The Renal Histopathological Spectrum of Patients with Nephrotic Syndrome Presenting to Nephrology Division Khyber Teaching Hospital, Peshawar, Pakistan - Raza, Ali; Tahir, Maria; Khattak, Aaliyan; Hassan, Essa; Noman, Muhammad; Mushtaq, Wisha (Indus Journal of Bioscience Research, 2024)
Introduction: This study investigated the renal histopathological patterns in nephrotic syndrome patients who underwent renal biopsy at the Department of Nephrology, Khyber Teaching Hospital, between March 2023 and October 2024. It aimed to identify the underlying glomerulopathies responsible for nephrotic syndrome in these patients Methodology: The study included 122 nephrotic syndrome patients, aged 7 to 69 years, categorized into four age groups. Renal biopsies were analyzed using light microscopy and immunofluorescence. The chi-square test assessed the association between histological variants and categorical variables such as gender and age groups primarily seen in females. Minimal Change Disease is significantly associated with younger individuals, particularly those under 24, with no cases in older patients, suggesting it predominantly affects pediatric or young adult populations. Results: Out of 122 patients, 80 (65.6%) were male and 42 (34.4%) females, with a mean age of 34.28 ± 14.81 years. Membranous Glomerulonephritis (35.2%) was the most common diagnosis, followed by Focal and Segmental Glomerulosclerosis (18.0%) and Lupus Nephritis (14.8%). Minimal Change Disease affected 10 patients, primarily younger individuals. HIV-Associated Nephropathy (0.8%) and Diabetic Nephropathy (1.6%) were the least frequent. Significant associations were found between histopathological variants and both age and gender (p-values 0.000 and 0.001, respectively), with Lupus Nephritis more common in females and Membranous Glomerulonephritis in males. These findings highlight age- and gender-specific trends Conclusion: Membranous Glomerulonephritis is most prevalent, especially in males and younger adults, while Lupus Nephritis is primarily seen in females. Minimal Change Disease is significantly associated with younger individuals, particularly those under 24, with no cases in older patients, suggesting it predominantly affects pediatric or young adult populations.